EFL Teachers’ TPACK Preparedness in Eastern Indonesia: Challenges and Strategies - Henry Latuheru; Hendrik Makaruku (Huele: Journal of Applied Linguistics, Literature and Culture, 2026)
This study investigated junior high school EFL teachers' Technological Pedagogical Content Knowledge (TPACK) preparedness in Ambon, Eastern Indonesia, and examined the challenges they encountered and the strategies they employed during online teaching in 2021. Grounded in Koehler and Mishra's TPACK framework, this study adopted a sequential explanatory mixed-method design. Data were collected through a TPACK questionnaire administered to 51 EFL teachers and semi-structured interviews with seven selected participants. Quantitative findings revealed that participants self-reported a high level of TPACK preparedness, with Technological Knowledge emerging as the weakest domain. Qualitative findings identified two major challenges: engaging students in online learning and maintaining motivation in virtual classrooms. To address these, teachers employed digital learning media, technology-based assessment, interactive instructional design, and online classroom management strategies. The findings underscore the need for context-specific professional development targeting teachers' technological competencies in resource-limited educational settings in Eastern Indonesia.